Climate Change In The Sub-Saharan Region: Impact, Transmission Channels And The Mitigation Effect From Financial Market Development On Carbon Emission - Mohamed, Abdinur Ali (2025)
Climate change poses a global challenge, impacting countries differently based on their geographical and economic contexts. African nations are particularly vulnerable due to their location and reliance on climate-sensitive sectors. The sub-saharan region faces significant economic risks from climate variability, affecting productivity, investment, and labor supply. Existing studies often overlook the complexity of these impacts and their transmission channels, lacking robust analyses of nonlinear relationships. This study aims to assess the impact of climate change on economic growth in sub-saharan africa, focusing on the nonlinear effects of temperature and rainfall. It also examines how financial market development can mitigate these impacts. Using data from 1994 to 2018 across 29 countries, the study employs instrumental variables and the lind and mehlum u-test to identify nonlinear relationships, alongside robustness checks to ensure result validity. Results indicate that moderate temperatures support growth, while extreme heat is detrimental. Rainfall positively influences growth, though heavy rainfall shows mixed effects. The study finds that financial development initially increases carbon emissions but reduces them at advanced levels. A nonlinear relationship between temperature and investment is confirmed.